Effect of "RIZOKOM-1" and "SERHOSIL" biopreparations on soil moisture in cotton development. (Texas Journal of Agriculture and Biological Sciences, 2023)
This article presents data on the dynamics of changes in soil moisture depending on the season during the cultivation of Namangan-77 cotton variety under the conditions of using the ecologically clean "RIZOKOM-1 and SERHOSIL" biopreparations created on the basis of beneficial bacteria and algae in the conditions of water-saving technologies. The obtained results showed that as a result of the use of biopreparations, it was determined that soil moisture can be preserved more than the control option. Experiments show 15-19% more soil moisture between each watering and 12-15 days longer retention time in satisfactory amounts for the plant